EVALUASI KINERJA CRUSHING PLANT DAN EXCAVATOR HITACHI ZAXIS 110 MF UNTUK PENGOPTIMALAN HASIL PRODUKSI DI PT. AMAN TOEBILLAH PUTRA, DESA TANJUNG BARU, KECAMATAN MERAPI BARAT, KABUPATEN LAHAT, PROVINSI SUMATERA SELATAN - Putri Irma; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT. Aman Toebillah Putra has a processing plant with a production target of 300 tons / hour. Whereas the January 2018 crusher report is not optimal. The less than optimal performance of the unit is caused by many factors that inhibit the work process of the processing plant. The impact of less optimal production from the crushing plant affects consumer demand for coal. So this is the background of the author to conduct an evaluation of the achievement of the crushing plant production target to meet the production target planned for 2018 at the crushing plant of PT. Aman Toebillah Putra. The type used in this study is the type of applied research. Where applied research is done with the intention of applying, implementing or testing theory by analyzing the supporting factors of the production of crushing plants such as cycletime, support tools, belt conveyors, actual field conditions such as ROM and stockpile conditions. Actual production of support equipment and crushing plant at PT. Aman Toebillah Putra is 127 tons/hour and 273.18 tons/hour for January 2018 and still does not meet the 2018 production target of 300 tons/hour. Availability of crushing plants with a mechanical avaibility value of 97%. Physicl avaibility value is 98%. The value of used of avaibility is 52%. The value of effective utilization is 51%. Availability of support with a mechanical avaibility value of 100%. Physical value is 100%. The value of used of avaibility is 51%. The value of effective utilization is 51%. To fulfill the 2018 production target of 300 tons/hour, an evaluation of the crushing plant and support of Hitachi Zaxis 110 MF excavators is carried out. Evaluation conducted for support tools is the replacement of Hitachi Zaxis 110 MF excavator which has a 0.5 m3 bucket size into a Caterrpilar 320C excavator with 0.9 m3 bucket size so that loading time can be faster, and support tools can still do other work so that production targets what the company wants can be achieved. Whereas for the crusher unit there is no further improvement because it supports the company's production target of 300 tons/hour. Keywords: Production, Losstime, Optimal Time, Coal Mining, Crusher